Projections of expenditure for public hospitals in Ireland, 2018-2035, based on the Hippocrates Model - Conor Keegan; Aoife Brick; Adele Bergin; Maev-Ann Wren; Edward Henry; Richard Whyte (The Economic and Social Research Institute (ESRI), 2020)
New research from the ESRI provides projections of expenditure for public acute hospital and adult acute psychiatric in-patient services in Ireland for the years 2018-2035. These projections are based on new ESRI projections for population and economic growth, both of which consider the impact of COVID-19. A range of alternative projections are presented reflecting alternative assumptions about population growth, trends in health and life expectancy, policy change, and costs. The report contains the most comprehensive mapping of Irish public hospital expenditure to have been published.
Keywords: 330; Gesundheitskosten; Krankenhausfinanzierung; Irland